Parameterised Complexity of Model Checking and Satisfiability in Propositional Dependence Logic - Mahmood, Yasir; Meier, Arne (Lecture Notes in Computer Science)

DeepWind: An Accurate Wind Turbine Condition Monitoring Framework via Deep Learning on Embedded Platforms - Ghasemzadeh Mohammadi, Hassan; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Kuschel, Maurice; Jentzsch, Felix Paul; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Global generalized solutions to a forager–exploiter model with superlinear degradation and their eventual regularity properties - Black, Tobias (Mathematical Models and Methods in Applied Sciences)
Keywords: Applied Mathematics; Modeling and Simulation

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Enhanced electrocatalytic oxygen evolution by manipulation of electron transfer through cobalt-phosphorous bridging - Pan, Ying; Ren, Hangjuan; Chen, Ruizhe; Wu, Yanfang; Chu, Dewei (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar A.; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

An Algorithmic Solution for Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef (the International Journal On Advances in Software)

Zirkel und Lineal ohne Parallelenaxiom: Ein konstruktiver Zugang zur hyperbolischen Geometrie. - Hoffmann, Max (Der Mathematikunterricht)

Die Bedeutung unterschiedlicher Heterogenitätsmerkmale für das Erleben von Zustandsangst vor dem Sportunterricht in der Grundschule - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J. (Grundschulsport. Empirische Einblicke und pädagogische Empfehlungen)